Artificial Intelligence in Digital Marketing Strategies in the UAE: The Mediating Role of Predictive Analytics in Enhancing Customer Conversion - Vij, Mohit; Vij, Anu; Kumar, Pranav; Masoud, Emad Y.; Al Kurdi, Barween; Alzoubi, Haitham M. (International Review of Management and Marketing, 2025)
Recent studies investigate the fundamental influence of Artificial Intelligence on UAE digital marketing practices designed to maximize customer acquisition. The rising dependence on automated systems and learning models and data-driven automation has led businesses in the UAE to implement AI systems to build personalized consumer transactions and optimize promotional activities along with demand forecasting. AI achieves confirmed benefits with its own methods yet its power to transform real customer acquisitions depends on predictive analytics as an intermediary solution. The present research evaluates predictive analytics because it functions as an essential interconnection between AI systems and improved customer conversion rates. A survey research design involving 287 marketing leaders and digital strategy experts operating in different industries throughout the UAE will be utilized for data collection. The SEM modeling analysis will evaluate the direct relationships as well as the mediating relationships present in the dataset. This research will deliver extensive evidence regarding how AI systems unite with predictive analytics to generate loyal customers in the UAE digital marketplace.